Awaken the Giant Within : How to Take Immediate Control of Your Mental, Emotional, Physical & Financial Destiny - Robbins, Anthony (Rawalpindi, Pakistan Service Book Club, 2014)
Author shows how to take immediate control of mental, emotional, physical, and financial destiny with strategies from his Date with Destiny seminar.
Include Index and Illustration
Keywords: Success--Psychological aspects -- Control (Psychology) -- Self-actualization (Psychology)